Design and fabrication of adjustable and portable 4- legs walker - Nurul Ariffah, Hamidi (2012)
This report present about the 4-legs walkers that always been used especially for the elders and the injured person. A walker or walking frame is a tool for disabled or elderly people who need additional support to maintain balance or stability while walking. The use of this equipment is to the person walks with the frame surrounding their front and sides and their hands provide additional support by holding on to the top of the sides of the frame. Traditionally, a walker is picked up and placed a short distance ahead of the user. The user then walks to it and repeats the process. With the use of wheels and glides, the user may push the walker ahead as opposed to picking it up. This makes for easier use of the walker, as it does not require the user to use their arms to lift the walker. This is beneficial for those with little arm strength. A walker is a good tool for those who are recuperating from leg or back injuries. It is also commonly used by persons having problems with walking or with mild balance problems. In designing such a medical product or thing for the human use, the anthropometric data is the important element that must be put in consideration. It is refer to the measurement of the human individual. In design of any product or workspace, anthropometric data is actually being utilized although sometimes the designer is unaware of it. Without using the appropriate measurements or limits, the product, layout or workspace may not function, or function but not as effective as it should be. It may also look awkward, not in proportion or not appealing aesthetically. The idea of the fabricating of this walker is based on student creativity. Materials are proposed for the fabrication of the walker is mild steel and the aluminium. In this report, we’ll also be having more to the fabrication of this walker. The development during the project is to fulfil the learning objective that to produce the adjustable and portable 4-legs walker according to the anthropometric data. The variety of applications from the project can be use to produce a product based on anthropometric data.